The role of the National Commission on Violence Against Women: A Domestic Violence Case Study - Rahmadiany, Adisti; Balqis, Arale; Rachmawaty, Artika Ridha; Sembiring, Salsabilla Zahwa; Aji, Muhammad Prakoso (Pusat Studi Gender dan Anak, 2024)
The National Commission of Woman is an independent institution that focuses on the issue of violence against women, including domestic violence. This research aims to analyze the role of the National Commission on Violence against Women in domestic violence cases. The research method used is qualitative research with data collection techniques in the form of semi-structured interviews and literature studies, as well as data analysis using an interactive model. The National Commission on Violence against Women's process for domestic violence cases includes complaints, reception, gender-based identification, follow-up, and referral. If obstacles occur, an action will be taken. Various internal and external challenges are factors that hinder the effectiveness of the role of the National Commission on Violence against Women. Apart from that, according to annual records, domestic violence cases in 2020 and 2022 will increase due to several factors. Therefore, The National Commission of Woman is committed to protecting and fighting for the rights of domestic violence victims to get justice and a decent life.